2016
DOI: 10.1109/tvt.2015.2413790
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive-Truncated-HARQ-Aided Layered Video Streaming Relying on Interlayer FEC Coding

Abstract: Abstract-Inter-layer forward error correction coding (IL-FEC) constitutes an effective unequal error protection (UEP) scheme conceived for transmitting layered video over wireless channels. In contrast to traditional UEP schemes, it operates by embedding extra information concerning the base layer (BL) into the enhancement layers (ELs) without requiring extra transmission resources. The received EL packets assist in the decoding of the BL in order to reduce the distortion of the reconstructed video. The optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The maximum number of transmissions is changed based on the importance of the packet for LTE networks in [34], [35]. The authors in [36] considered interlayer FEC and HARQ, and found the best FEC code rate distribution among the video layers to minimize the video distortion. In [37], retransmissions are used for the base layer to reduce network congestion.…”
Section: B Video Transmission With Harqmentioning
confidence: 99%
“…The maximum number of transmissions is changed based on the importance of the packet for LTE networks in [34], [35]. The authors in [36] considered interlayer FEC and HARQ, and found the best FEC code rate distribution among the video layers to minimize the video distortion. In [37], retransmissions are used for the base layer to reduce network congestion.…”
Section: B Video Transmission With Harqmentioning
confidence: 99%
“…Reed-Solomon (RS) codes or Luby transform (LT) codes are invoked for mitigating the packet loss events at the application layer [67]. By contrast, the bit-level arrangements operate at the physical layer and rely on soft-decoded FEC codes for correcting bit-errors in wireless scenarios [47], [68], [69]. Specifically, the authors of [47] proposed a bit-level inter-layer coded FEC (IL-FEC) scheme that embeds the BL into the FEC coded ELs, so that the reception of the BL can be improved with the aid of the ELs using soft decoding.…”
Section: B Overview Of Unequal Error Protected Video Transmissionmentioning
confidence: 99%
“…Second, the FEC solutions [14][15][16][17][18] provide a certain level of reliability but also induce higher bandwidth consumption (e.g., 20 − 50% redundancy) and larger coding latency. Third, the HARQ (Hybrid ARQ) methods [30] [46] are conventionally plagued with the deficiencies of both FEC and ARQ schemes. Thus, the real-time and reliability performance of the existing error-control solutions are still inadequate to achieve excellent real-time video quality.…”
Section: Introductionmentioning
confidence: 99%